Blunt renal trauma-induced hypertension in pediatric patients: a single-center experience - Marcou, Marios; Galiano, Matthias; Jüngert, Jörg M.; Rompel, Oliver; Kuwert, Torsten; Wullich, Bernd; Hirsch-Koch, Karin (Journal of Pediatric Urology, 2021)
Purpose: Children have a greater chance of sustaining a renal injury than adults and higher odds of having a high-grade renal injury. Hypertension is a rare complication of blunt renal trauma, with risk being higher in cases of major renal trauma. We reviewed the cases of pediatric blunt renal trauma-induced hypertension in our tertiary referral center in an attempt to better understand this rare condition. Study design: A retrospective evaluation of children under the age of 18 who were admitted to our department during the last 20 years and were diagnosed with blunt renal trauma. Results: Twenty-three children presented with blunt renal trauma, one of whom was treated with emergency nephrectomy. Four children (18%) developed post-traumatic hypertension. All four cases were associated with a reduction in blood flow to the kidney, either through injury to the renal artery (in three cases) or through extrinsic compression of the kidney by a large perirenal hematoma (Page kidney; in one case). The Page kidney case developed hypertension during the initial hospitalization, and it resolved spontaneously after five months through the gradual resorption of the perirenal hematoma. Among the three cases of renal artery injury, hypertension during the initial hospitalization was only observed in one case, with hypertension in the other two cases manifesting after two months and four years, respectively. All three cases of renal artery injury resulted in a complete loss of function of the injured kidney, and two cases were treated with nephrectomy. Following nephrectomy, the blood pressure level returned to normal within a few days. Discussion: Development of hypertension following a blunt renal trauma can be heterogenous, with the time of manifestation stretching between days after the accident and years thereafter. Children have a higher risk of renal trauma and, according to published data out of the National Trauma Data Bank, a 20-times higher risk of renal artery injury in comparison to the adult population. Large multicenter studies are required to answer the question of whether children are therefore more prone to blunt renal trauma-induced hypertension than adults. Conclusions: Our study highlights the importance of blood pressure monitoring in children following blunt renal trauma, as post-traumatic hypertension can develop even years after the accident. In cases of a poorly functioning kidney, nephrectomy may be regarded as a curative therapy.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Accidents; Blood pressure; Child; Renal artery; Renovascular hypertension